Affect of urban design aspect in the urban spaces creation - Tafahomi, Rahman (2007)
The aim of this paper is to discuss the urban design aspects in new urban development of cities. Process of urban development Iranian cities is unable to create the quality in urban spaces. Some parts of the traditional urban spaces were damaged except for a few. The urban development follows the modernist model after the 1900s. The Master Plan in 1963s and the Development Plan of City and Surrounding Area in 1974s have less aspects of urban design knowledge. Therefore, in the new developments and intervention in the traditional parts of cities could not create quality urban spaces. Method of the study is by reviewing the content of urban development plans in Iran and recognition of the failures and shortages of urban design. In the survey of Mashhad in the northeast of Iran, the quality of urban spaces and the affect of this type of plans were analyzed qualitatively. It was anticipated in the study during the revision of the content of urban development plans and mixture of the urban design aspects can create new approach for simultaneous design in urban spaces of cities and the creation of quality urban spaces. The results of the research will be a new content of urban development plan. In this new type of content of plans there are design approaches in creating urban spaces as a result of urban design. Proquct of this research can be useful to change the situation of urban spaces in the Iranian city because with the new knowledge of urban design, the urban spaces and public realm will be important indicators of quality of the life in the cities as the physical expression of democratization of public sphere.